The lived experience of rejection sensitivity in ADHD - A qualitative exploration - Annabel Rowney-Smith; Beth Sutton; Lisa Quadt; Jessica A. Eccles (PLoS ONE, 2026)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental condition, commonly associated with differences in attention, and/or hyperactivity and impulsiveness. A lesser known, but highly impactful characteristic of ADHD is emotional dysregulation, which causes difficulties in emotional expression and identification. An aspect of emotional dysregulation which remains relatively unexplored in ADHD, is rejection sensitivity. In people who experience rejection sensitivity, perceived rejection and/or criticism can evoke extreme dysphoria. To investigate the lived experience of rejection sensitivity in ADHD individuals, five undergraduate students participated in focus-group interviews. The subsequent thematic analysis revealed three key themes which encapsulated their experiences; withdrawal , masking , and bodily sensations . The participants explained how rejection sensitivity elicited unpleasant bodily sensations, anxiety, and misery, and how, in turn, they used masking to camouflage these feelings. They then discussed how the use of masking had caused them to become dissociated from themselves and to withdraw from others, which often resulted in loneliness. It was apparent that rejection sensitivity significantly impacts mental wellbeing, eliciting feelings such as anxiousness, despair, and embarrassment. In turn, social function is significantly impaired, alongside career opportunities, and daily life. Our findings indicate a need for deeper understanding of ADHD traits and emotional dysregulation, which may in turn lessen the presence of rejection sensitivity in ADHD individuals.